The bizarre male of Spalangia dozieri (Hymenoptera: Pteromalidae): adaptations for male phoresy or the result of sexual selection? - Gibson, Gary A. P.; Reigada, Carolina [UNESP] (Entomol Soc Canada, 2009)
Spalangia dozieri Burks is newly recorded as a gregarious parasitoid in the puparia of Chrysomya albiceps (Wiedemann), C. putoria (Wiedemann). Lucilia eximia (Wiedemann), and L. sericata (Meigen) (Diptera: Calliphoridae), and represents the first report of gregariousness in Spalangia Latreille. The previously unknown males of S. dozieri are described and compared with females. Males have highly modified legs and several other sexually dimorphic features that differ front those of other Spalangia species. Most of the Unusual features are hypothesized to be adaptations for grasping and holding and it is suggested that males either are phoretic on adults of their dipteran hosts or, possibly. that males exhibit aggressive or other atypical behaviour toward siblings that is correlated with being gregarious. Barbados, Brazil, Dominica, St. Lucia. St. Vincent. and Trinidad are recorded as new Country distribution records for S. dozieri.